Modern Training of Students of Uzbek Musical Instruments and Makom Players in the General Piano Class - Madaminovna, Karimova Mavluda (Researchparks Publishing, 2023)
Teacher - Student - Progress - Future! Such capacious words mean the development and improvement of the most important wealth in the life of society, the country - the young generation in general and each in particular. Educator, teacher. These are special people on whom a special mission is assigned - the formation of personality, the training of a profession. The future of the country depends on their activities. The cultural, spiritual, moral component of this wealth is in our hands. To increase it is our great task.